COMPOSITION, STABILITY, AND STRUCTURE OF A NEW MEMBER OF THE AENIGMATITE GROUP, NA2MG(4+X)FE(2-2X)3+SI(6+X)O20, SYNTHESIZED AT 13-14 GPA - Gasparik T.; Parise J.B.; Reeder R.J.; Young V.G.; Wilford W.S. (My University, 1999)
A new phase isostructural with the minerals of the aenigmatite group Na2Mg41xFe Si61xO20 with x 5 0.25 2 0.5 was synthesized at 13-14 GPa with a split- 31 222x sphere anvil apparatus (USSA-2000). The structure (for x 5 0.4) was determined from twinned-crystal X-ray diffraction data. The unit cell is triclinic, P1, a 5 10.328(1), b 5 10.724(1), c 5 8.805(1) A ˚, a5 105.15(1), b5 96.85(1), g5 125.47(1)8, V 5 719.67(3) A ˚ 3 , Z 5 2, calculated density 5 3.335 g/cm 3 . The twin law, independently determined from electron diffraction and transmission electron microscopy and by inspection of the X-ray data collected with an area detector, relates the twin components by a 1808 rotation about (110)*. Due to the coupled substitution, 2Fe 31 5 MgSi, which introduces octahedral Si, the stability of the phases with the aenigmatite structure apparently expands with in- creasing pressure. Hence, these phases could play a major role in the transition zone (410- 660 km), where the more common minerals they are replacing, olivine and clinopyroxene, reach the limit of their stability. The new evidence for the stability of aenigmatite-like minerals in the deep mantle could have important implications for the origin of the parental magmas producing aenigmatite-bearing and other agpaitic rocks.